2021
DOI: 10.13057/biodiv/d220217
|View full text |Cite
|
Sign up to set email alerts
|

The role of coastal biodiversity conservation on sustainability and environmental awareness in mangrove ecosystem of southern Malang, Indonesia

Abstract: Abstract. Abidin Z, Setiawan B, Muhaimin AW, Shinta A. 2021. The role of coastal biodiversity conservation on sustainability and environmental awareness in mangrove ecosystem of southern Malang, Indonesia. Biodiversitas 22: 648-658. Southern coast of Malang, East Java, Indonesia has several mangrove ecosystems used for ecotourism, such as Clungup Mangrove Conservation Tiga Warna (CMC Tiga Warna). This area has consistently implemented ecotourism principles. Previously, it was assumed to be vulnerable from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 32 publications
0
10
0
7
Order By: Relevance
“…Previous study Abidin et al., (2020) reported that coastal biodiversity conservation strategy has been focused on maintaining a balance between nature's ability and its restricted use through ecotourism as part of the coastal ecosystem performed in CMC Tiga Warna ecotourism. It applies the two ecotourism destination zonings of: (1) emission-free areas, consisting of the application of pedestrian paths, and the application of motorized vehicle lanes; and (2) limited use for ecotourism in mangrove conservation area and coral reef protected areas.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous study Abidin et al., (2020) reported that coastal biodiversity conservation strategy has been focused on maintaining a balance between nature's ability and its restricted use through ecotourism as part of the coastal ecosystem performed in CMC Tiga Warna ecotourism. It applies the two ecotourism destination zonings of: (1) emission-free areas, consisting of the application of pedestrian paths, and the application of motorized vehicle lanes; and (2) limited use for ecotourism in mangrove conservation area and coral reef protected areas.…”
Section: Resultsmentioning
confidence: 99%
“…Clungup Mangrove Conservation (CMC) Tiga Warna has become one of Malang Regency's coastal ecotourism sites, as well as one of Indonesia's coastal places that regularly maintains mangrove and coral reef conservation. Ecotourism management has consistently prioritized ecological protection above the use of limited natural resources for ecotourism ( Abidin et al., 2021 ). The increasing number of tourist visits in 2019 was viewed as more aggressive.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that many animals represented in the analyzed coats of arms are quite common. Rare and endangered species (e.g., Litvinov et al, 2018) are also represented, but not so frequently (Table 2), despite the decline in some mammal species that is registered in Russia (Howe et al 2012;Bragina et al 2015), not speaking of birds, insects, invertebrates, etc. Moreover, the coats of arms seem to be more suitable for increasing the public awareness of animals, not plants.…”
Section: Discussionmentioning
confidence: 99%
“…Various aspects of this topic were addressed by numerous experts, including Kassas (2002), Martín-López et al (2009), Clements (2013), Lee and Iwasa (2014), Opermanis et al (2015), Lundberg et al (2019), and Dimopoulos and Kokkoris (2020). Additionally, the rich biodiversity of a given territory is an important ecotourism resource, rational exploitation of which also requires the increased awareness of visitors (Meletis and Harrison 2010;Olmsted et al 2020;Abidin et al 2021). Because of this, it appears to be highly important to actively promote the knowledge of territorial biodiversity through various 'channels' and with various approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Sebaliknya jika kondisi ekowisata CMC mengalami degradasi pada sumberdaya alamnya dan tidak dijaga dengan baik, maka kesadaran masyarakat setempat terancam menurun karena tidak lagi memperoleh manfaat ekonomi dari pariwisata. Dengan demikian, peran konservasi dalam menjaga keberlanjutan sumberdaya alam sangat berperan untuk meningkatkan efektifitas ekowisata (Abidin et al, 2021).…”
Section: Analisis Daya Dukung Kawasanunclassified